‘Power with:’ We know it’s important, but how do we measure it? - Meinzen-Dick, Ruth S.; ElDidi, Hagar; Pereira, Audrey; Heckert, Jessica; Kosec, Katrina; Nchanji, Eileen; Seymour, Greg; Doss, Cheryl (International Livestock Research Institute, 2024)
Collective agency, or ‘power with,’ is fundamental to feminist approaches to empowerment—group-based approaches are common, but there are surprisingly few accepted measures of collective agency. The working paper ‘Power with:’ conceptualizing and measuring women’s collective agency addresses this gap.